The Effect of Service Quality, Tax Sanctions, and Modernization of the Tax Administration System on Taxpayer Compliance - Adissya Hawalia Husni; Elprina Sarah Azahra; Noor Jaesmine Maharani (Yayasan Az Zukhruf Cendikia, 2025)
Purpose - This study aims to examine the influence of Service Quality, Tax Sanctions, and Tax Administration System Modernization on Taxpayer Compliance. Design/methodology/approach - This study uses quantitative research methods, using primary data collected from a population of 64 respondents from Individual Taxpayers in the city of Bekasi. Data analysis was carried out using Partial Least Square (PLS) software with Moderated Regression Analysis. Findings - The results of this study found that Service Quality has a positive effect and has a non-significant effect on Taxpayer Compliance, Tax Sanctions have a positive effect and have a significant effect on Taxpayer Compliance, and Modernization of the Tax Administration System has a positive effect and has a significant effect on Taxpayer Compliance Limitations/implications of the study - This study introduces innovative variables in taxpayer compliance, especially service quality, tax sanctions, and modernization of the tax administration system, which provides new insights. However, this finding is limited because the variables are measured using a questionnaire, the data obtained is the perception of respondents of the data obtained through WhatsApp so that the questionnaire obtained is not guided in detail in its filling.